GIBBERELIC ACID ALONE OR ASSOCIATED WITH WAX IN THE POST-HARVEST OF TAHITI LIME - BIASI, Luiz Antonio; ZANETTE, Flávio (Scientia Agraria, 2000)
The colour conservation of the peel green of the lime Tahiti is very important for its commercial value and its possible by application of products that avoid the chlorophyll degradation. ). With the aim to study the effect these products in fruit rippening, to increased the fruit conservation, this work was carried out with fruit collected in a orchard located in Marília, SP and installed at 07/11/1998 in Curitiba, PR. The treatments were the following: 1) control; 2) GA3 (100 mg.L-1); 3) GA3 (200 mg.L-1); 4) GA3 (400 mg.L-1); 5) GA3 (100 mg.L-1)+ wax; 6) GA3 (200 mg.L-1) + wax; 7) GA3 (400 mg.L-1) + wax. The experimental desing was completely randomized with three replicates and 16 fruits per plot. The GA3 was applicated by immersion for two minutes in the solutions and the wax was applicated six hours after. The fruits were stored in polyethylene bags with 16 perforations at 7ºC. The evaluations were maded each 15 days. The GA3 and wax application had no effect in the juice biochemistry characteristics (pH, soluble solids and acidity). There was an acidity decrease and a pH increase during the storage period in all treatments. The GA3 application was efficient to delay the degreening. All the concentrations of GA3 were higher than control and didnt differ among theyself in relation the total chlorophyll. The degradation of chlorophyll showed the same tendency in all treatments with quadratic comportment. The degradation was 50% in the first 15 days. The fruits treated with GA3 showed about 33% of chlorophyll degradation at 30 days, while the control lost 57%. The relation of chlorophyll a/b increased until 30 days and decreased after. The conclusion is that GA3 at 100 until 400 mg.L-1 is efficient to avoid the degreening of lime Tahiti independent of wax application.